CONCEPTUAL METAPHOR IN THE POETRY ENTITLED LOVE SONGS BY SARA TEASDALE - Ni Putu Mitha Karunita; Ida Bagus Gde Nova Winarta; I Wayan English Study Program Faculty of Foreign Juniartha (PROJECT (Professional Journal of English Education), 2022)
The article entitled "Conceptual Metaphor In the Poetry Entitled Love Songs by Sara Teasdale" focuses on finding the types of metaphors in Sara teasdale's poetry. This research aims to find the types of metaphors and also to analyze what meanings are contained in the lyrics of the Love Song poem. This topic is part of Figurative Language which aims to convey a message imaginatively and figuratively. The data obtained were analyzed using the theory of Lakoff and Johnson (2003) and to analyze the meaning contained in each data found, the authors used the theory of Leech (1981). This study uses the observation method in collecting data and using qualitative methods in analyzing the data. The results of the analysis found a total of 26 metaphorical data, of which 10 data contained structural metaphors, 10 data contained orientational metaphors and 6 data contained ontological metaphors. From all the data collected, the authors found 1 type of meaning, namely connotative meaning. Keywords:  Poetry, Metaphor, Meaning